MATAWAI AMAHU PADA NJARA HAMU: Kesadaran akan Harmonisasi Kehidupan Ciptaan di Tanah Marapu - Djera, Adelvia Tamu Ina P. (Universitas Kristen Satya Wacana, 2016)
Knowledge and technology keep on developing while environmental need to struggle on problems that becoming important issue on globalization era. Sumba, a traditional iland in Indonesia also try to keep up with the development of worldwide technology. This paper is trying to describe and analyze one of the life philosophies of Sumba people, “matawai amahu pada njara hamu” in order to understand and interpret the existence nature and all the creations in the midst of the development progress situation holistically. Based on this philocophy concept, cross-faith communities in East Sumba can find common ground for harmonizing life of creation (eco-human soterio). Therefore, this philosophy must be strived to be a shared awareness (ecosophy) of the interfaith communities, because the Land of Marapu is a shared responsibility. This awareness will guide Sumba people to treat nature and all creations ethically (eco-ethic).